'Out of the box': A child-led emotional wellbeing project. (2nd June 2019) - Thrupp, Eve
Abstract : Sometimes thinking outside the 'box' can help develop creative solutions by looking at situations from another point of view.Eve Thrupp shares her experience of developing a child-led intervention aimed at improving emotional resilience in primary school-aged children.